Cultural Dynamics and Social Representations of Dogs in the Inuit Community of Kuujjuaq (Nunavik) - Francis Lévesque; Patricia Brunet (Études Inuit Studies, 2019)
This article presents the highlights of field research carried out in Kuujjuaq (Nunavik) in September 2016. Its main objective is to create a general portrait of the place that dogs occupy in this community, among both Inuit and non-Inuit. Although the dog’s place in traditional Inuit culture is well known and documented, the place he has occupied since Inuit have settled and began using snowmobiles and sharing their living environment with non-Inuit remains poorly understood. By questioning the cultural and social place of the dog in a community where Inuit and non-Inuit live together, this research attempts to highlight the different dynamics related to dogs and gain a better understanding of what dogs are for the locals of Kuujjuaq. This article concludes that resources for dogs and their management are limited and still focused on health and human security, and that dogs in the community occupy a position that oscillates between appreciation and repulsion—a position shaped by cultural and community contexts. Cet article présente les faits saillants d’une recherche de terrain effectuée à Kuujjuaq (Nunavik) en septembre 2016. Son principal objectif est de dresser un portrait général de la place du chien dans cette communauté, tant auprès des Inuit que des non-Inuit. Si la place du chien dans la culture inuit traditionnelle est bien connue et documentée, celle que le chien d’aujourd’hui occupe depuis que les Inuit se sont sédentarisés, qu’ils utilisent la motoneige et qu’ils partagent leur milieu de vie avec des non-Inuit demeure mal comprise. En questionnant la place culturelle et sociale du chien dans une communauté où les populations Inuit et non-Inuit cohabitent, cette recherche tente de faire ressortir les différentes dynamiques reliées aux chiens et vise à acquérir une meilleure compréhension de ce que sont les chiens pour les habitants de Kuujjuaq actuellement. Cet article conclut que les ressources destinées aux chiens et à leur gestion sont limitées et toujours axées sur une perspective de santé et ...